Factors influencing the levels of exhaled carbon monoxide in asthmatic children. (November 2014) - Jesenak, Milos; Banovcin, Peter; Havlicekova, Zuzana; Dobrota, Dusan; Babusikova, Eva
Abstract Objective: Bronchial asthma is characterised by chronic airway inflammation commonly associated with increased oxidative stress. Exhaled carbon monoxide (eCO) levels could act as markers of both oxidative stress and allergic inflammation. We aimed to study eCO levels in asthmatics and detect the possible factors influencing them. Methods: We studied 241 asthmatic children and 75 healthy children. The differences in eCO levels among various asthmatic phenotypes and the correlations between eCO and other measured parameters (spirometric indices, Asthma Control Test score, exhaled nitric oxide, total IgE, blood eosinophils and marker of oxidative damage of proteins) were analysed. Results: Levels of eCO widely differed according to the selected characteristics of asthma. Asthmatics showed higher eCO concentrations than controls (1.44 ± 0.12 ppm vs. 0.91 ± 0.11 ppm, p < 0.001). Acute exacerbation of asthma was accompanied by a significant increase in eCO compared to the clinically controlled stage (2.17 ± 0.36 ppm vs. 1.33 ± 0.13 ppm, p < 0.001). Atopic, non-atopic asthma and asthma associated with allergic rhinitis (AR) showed elevated levels of eCO. The levels of eCO negatively correlated with the marker of protein oxidation in asthmatics, especially in atopic form and during acute exacerbation. Conclusions: In a population of asthmatic children, eCO levels could be considered as a marker of both allergic inflammation and oxidative stress in the airways. Concomitant AR and asthma control were the most important factors affecting the levels of eCO in asthmatic children. However, our results do not support the use of routine eCO in the clinical practice.